Analisis Citra Merek dan Kepercayaan Merek terhadap Loyalitas Pelanggan Pada PD. Ikram Nusa Persada Kota Sukabumi - Reza Eka Perdana; Kokom Komariah; Faizal Mulia (IPM2KPE, 2020)
The purpose of this study is to analyze brand image and brand trust towards customer loyalty in PD. Ikram Nusa Persada, Sukabumi City, knows how the brand image of PD. Ikram Nusa Persada, Sukabumi City, knows how the brand believes in PD. Ikram Nusa Persada Kota Sukabumi, knowing how customer loyalty to PD. Ikram Nusa Persada, Sukabumi City, knows how much influence the brand image and brand trust have on customer loyalty in PD. Ikram Nusa Persada, Sukabumi City. The method used in this study is to use random sampling by distributing 66 questionnaires to PD customers. Ikram nusa persada. The results of the study show that the results of data analysis obtained in the brand image F test (X1) and brand confidence (X2) on customer loyalty (Y) show that the calculated Fcount value is greater than the Ftable value. Conclusions, the influence of brand image and customer loyalty on customer loyalty can positively and significantly affect customer loyalty PD dolphin stamp wax products. Ikram Nusa Persada. Keywords: Brand Image, Brand Trust, Customer Loyalty